Influence of Temperature and Nutrients on the Growth Rate of the Marine Diatom, Skeletonema costatum (Greville) Cleve 1873 - Vlas, Oana; Lazăr, Luminita; Boicenco, Laura; Pantea, Elena; Făgăraș, Marius (Cercetări Marine - Recherches Marines, 2020)
Skeletonema costatum is a species of microalgae that often produces blooms worldwide, which have led to mortality among fish and imbalances in the ratio of nutrients in the water column. The effect of temperature on the growth of S. costatum was examined under temperatures between 8 and 20°C. Also, the effect of nitrogen to phosphorus ratios on the growth of S. costatum was examined under Redfield ratio, nitrogen limitation and phosphorus limitation ratios. The diatom was able to grow in all the tested conditions, but the highest growth rates were reached at a temperature range of 17.7-18.8°C and phosphorus limitation conditions. Our study highlighted the fact that this species, the main responsible for the most intense and longest annual process of massive phytoplankton development can tolerate a wide range of nitrogen and phosphorus concentrations (at both limits) and a wide range of temperatures. These results point out that S. costatum can be considered an opportunistic species, with high potential to cause harmful blooms worldwide.